006 PP: LISTENING TO PARENTS: MIX-METHODS EVALUATION OF THE KEY WORKER ROLE. Issue 4 (12th April 2015) - Martins, A; Aldiss, S; Taylor, R; Gibson, F
Abstract : Understanding how interventions work in the real world of practice has motivated the use of qualitative methods in evaluation of interventions in health care. a A complex intervention may operate differently in practice from the original intention and qualitative research can address how an intervention is used in practice while quantitative research is used to measure outcomes. b This paper describes the practical application of a mix-methods approach in the evaluation of a nurse specialist key worker role in children's cancer care across the UK with reference to parents' views of the role. Using this study as example, methodological issues are explored about the use of the interview/questionnaire approach in the evaluation, as well as a brief consideration of combining methods. The nurse specialist key worker role was funded in eighteen Principal Treatment Centres across Scotland, Wales and England. Ninety parents took part in the questionnaire and out of these 20 took part in an individual semi-structured interview. The information from the questionnaires helped identify the family's needs and the support received; it did not show, however, how contextual constraints and families' individual needs helped shape the way the key worker role was developed and the impact it had on families. The interviews allowed the researcher to pick up on these issues. In particular, the interviews expanded the breadth of understanding on how the key worker supported the families, what activities occurred under what conditions, and who carried out the activities. The depth of the analysis and understanding of the impact of the key worker role was only achieved by the combination of methods used. The questionnaire allowed the evaluation of the role in specific outcomes and the interviews helped us identify and understand the influencing factors/conditions needed to achieve the outcomes. a O'Cathain A, Murphy E, Nicholl, J. Why, and how, mixed methods research is undertaken in health services research in England: a mixed methods study. BMC Health Services Research 2007;7:85. b Parry-Langdon, N., Bloor, M., Audrey, S., et al . Process evaluation of health promotion interventions. Policy & Politics 2003;31:207–16.